2021
DOI: 10.1007/s00330-021-07846-5
|View full text |Cite
|
Sign up to set email alerts
|

Irreversible electroporation (IRE) in renal cell carcinoma (RCC): a mid-term clinical experience

Abstract: Objectives To evaluate the safety and efficacy of CT-guided IRE of clinical T1a (cT1a) renal tumours close to vital structures and to assess factors that may influence the technical success and early oncological durability. Methods CT-guided IRE (2015–2020) was prospectively evaluated. Patients’ demographics, technical details/success, Clavien-Dindo (CD) classification of complications (I–V) and oncological outcome were collated. Statistical analysis was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Interestingly, a tertiary lymphoid‐like structure was observed (red arrow), which has been reported to favor the outcome of immunotherapy. [ 26 ] It should be noted that IRE has also been used in the clinical and preclinical treatment of liver, [ 27 ] breast, [ 28 ] renal cancers, [ 29 ] etc. To test if our findings could extend to other tumor types, the treatment regimens were further evaluated in orthotopic 4T1 murine breast cancer model with a positive TGF‐ β expression (Figure S5 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a tertiary lymphoid‐like structure was observed (red arrow), which has been reported to favor the outcome of immunotherapy. [ 26 ] It should be noted that IRE has also been used in the clinical and preclinical treatment of liver, [ 27 ] breast, [ 28 ] renal cancers, [ 29 ] etc. To test if our findings could extend to other tumor types, the treatment regimens were further evaluated in orthotopic 4T1 murine breast cancer model with a positive TGF‐ β expression (Figure S5 , Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…We prospectively evaluated CT [ 37 ]—it navigated IRE and showed suboptimal results and acceptable complications ( Table 1 ). Thirty RCC tumors with an average size of 2.5 cm were treated with this method and achieved a primary technique success rate of 73.3%, which improved to 97% after performing CA-7 residual disease.…”
Section: Resultsmentioning
confidence: 99%
“…In a study looking at thirty renal cell carcinomas treated with IRE over a median follow-up of 37 months, there was a technical success rate of 73.3%. 34 Because of the relatively lower technical success rate, this study suggested that IRE should only be used for cases where the tumour is close to critical structures.…”
Section: Choice Of Ablation Devicementioning
confidence: 93%